Therapeutic hyperthermia promotes lipid export and HSP70/90 during machine perfusion of human livers - Adam M. Thorne; Yana Geng; Veerle A. Lantinga; Marieke Smit; Jan Albert Kuivenhoven; Robert J. Porte; Folkert Kuipers; Peter Olinga; Justina C. Wolters; Vincent E. deMeijer (Physiological Reports)
Abstract Liver transplantation is the only curative option for end‐stage liver disease. Donor shortages necessitate the use of higher risk donor livers, including fatty livers, which are more susceptible to ischemia‐reperfusion injury. Machine perfusion has improved graft utilization and is typically performed at hypothermic (8–12°C) or normothermic (35–37°C) temperatures. Here we studied the impact of mild hyperthermia (40°C) as a therapeutic intervention for fatty livers using in‐depth proteomic and lipoprotein profiling of whole organ perfusion and precision‐cut liver slices. We observed proteomic changes with metabolic alterations over time, evidenced by a significant increase in lipid export in whole organ perfusions. Furthermore, PCLS showed significant upregulation of metabolic processes and heat shock protein response after 24 h of hyperthermia. Machine perfusion under hyperthermic conditions may be a potential strategy to improve the utilization of fatty liver grafts, ultimately expanding the donor pool and improving transplant outcomes.